Investigation of CD44 Gene Expression in People with Lung Cancer in Tehran - Zahra Ahmadzadeh Chaleshtari; noosha Zia-jahromi (Fasa University of Medical Sciences, 2020)
Background & Objective: CD44 is a cellular protein that has been extensively studied for carcinogenicity over the past decade, so the aim of this study is to investigate the expression of CD44 gene in people with lung cancer. Materials & Methods: 30 tissue samples were taken from the lung tumor and 30 samples were taken from healthy lung tissues. RNA samples were extracted and used for cDNA synthesis. The Real Time RT-PCR test with the GAPDH internal control gene was used to assess CD44 gene expression. Results: CD44 gene expression in tumor tissues, men, age group over 60 years, smokers and adenoma tumor, respectively 1.2, 1.4, 1.1, 1.9 and 1.1 times higher than healthy samples, women, age group Under 60 years of age, non-smokers had SCC tumors. Conclusion: Inflammation caused by lung cancer increased the production of CD44 inflammatory factor and thus increased its expression. Evaluating the expression of CD44 gene can be used as a marker to predict lung cancer.